Setting up and Managing Chain Initiatives - Storer, Christine; Dunne, A. (Wageningen Publishers, 2006)
Chain coordination is growing in importance to maintain access to global markets and competitive advantage. Of particular interest is how to set up and manage an initiative in a chain. Much of the research in the area of chains is based on case study examples of initiatives to improve chain performance. While this research is very rich in providing details about what was done, there can be questions of how applicable it may be in other situations. This research aimed to provide some more generalisable results that may be applied in a range of different situations.